Matrix Composition and Corridor Function for Austral Thrushes in a Fragmented Temperate Forest - Vergara-Egert, P (2013)
Although it is widely recognized that animal movement may be facilitated by corridors and hindered by the matrix, the influence of matrix composition on the use of corridors still remain poorly understood. We used translocation experiments and state-space models to assess if the movement response of the frugivorous bird, the austral thrush, to riparian forest strips varies depending on matrix composition (open pasture vs. eucalyptus plantation). In agricultural landscapes, the directions displayed by most birds when moving in the open pasture matrix were consistent with an edge-following behavior. Riparian strips also functioned as passive drift fences in agricultural landscapes, with strips being used as conduits for movements once birds entered into a riparian strip. Our results suggest that visual perception of riparian strips by birds is hampered by the complex habitat structure in the eucalyptus matrix and that the use of riparian strips as habitat is conditioned by the surrounding matrix. © 2012 Springer Science+Business Media Dordrecht.